The Migratory Properties and Numbers of T Regulatory Cell Subsets in Circulation Are Differentially Influenced by Season and Are Associated With Vitamin D Status - Lamikanra, Abigail A.; Tsang, Hoi Pat; Elsiddig, Shaza; Spencer, Michael; Curnow, Elinor; Danby, Robert; Roberts, David J. (Frontiers in Immunology, 2020)
The control of peripheral immune responses by FOXP3+ T regulatory (Treg) cells is essential for immune tolerance. However, at any given time, Treg frequencies in whole blood can vary more than fivefold between individuals. An understanding of factors that influence Treg numbers and migration within and between individuals would be a powerful tool for cellular therapies that utilise the immunomodulatory properties of Tregs to control pathology associated with inflammation. We sought to understand how season could influence Treg numbers and phenotype by monitoring the proportion of natural thymus-derived Tregs (nTregs) defined as (CD3+CD4+CD25+FOXP3+CD127-/low) as proportions of CD4+ T cells and compared these to all FOXP3+ Tregs (allTregs, CD3+CD25+FOXP3+CD127-/low). We were able to determine changes within individuals during one year suggesting an influence of season on nTreg frequencies. We found that, between individuals at any given time, nTreg/CD4+ T cells ranged from 1.8% in February to 8.8% in the summer where median nTreg/CD4 in January and February was 2.4% (range 3.75 to 1.76) and in July and August was 4.5% (range 8.81 to 3.17) p=0.025. Importantly we were able to monitor individual nTreg frequencies throughout the year in donors that started the year with high or low nTregs. Some nTreg variation could be attributed to vitamin D status where normal linear regression estimated that an absolute increase in nTreg/CD4+ by 0.11% could be expected with 10nmol increase in serum 25 (OH) vitamin D3 (p=0.005, 95% CI: 0.03 – 0.19). We assessed migration markers on Tregs for the skin and/or gut. Here cutaneous lymphocyte associated antigen (CLA+) expression on CD25+FOXP3+CD4+/CD4+ was compared with the same population expressing the gut associated integrin, beta7. Gut tropic CD25+FOXP3+beta7+Tregs/CD4+ had similar dynamics to nTreg/CD4+. Conversely, CD25+FOXP3+CLA+Tregs/CD4+ showed no association with vitamin D status. Important for cellular therapies requiring isolation of Tregs, the absolute number of beta7+ CD4+CD25+FOXP3+Tregs was positively associated with 25(OH)vitamin D3 (R2=0.0208, r=-0.184, p=0.021) whereas the absolute numbers of CLA+CD4+CD25+FOXP3+Tregs in the periphery were not influenced by vitamin D status. These baseline observations provide new opportunities to utilize seasonal variables that influence Treg numbers and their migratory potential in patients or donors.